To retaliate or not: a matter of cyber risk perception - Kaminska, M (2021)
This thesis investigates variation in state responses to hostile cyber operations. The central argument is that states’ strategic cultures and historical experiences shape their risk attitudes in cyber attack scenarios, with important consequences for their willingness (or not) to carry out meaningful punishment. To guide the empirical investigation, the thesis develops a conceptual framework drawing from and adapting the “risk society” theory in Sociology – an approach that has not yet been applied in cyber studies. The thesis explains weak state responses as a result of cultural and historical forces that produce sensitivities to the inherent risks and uncertainties of the operational environment of cyberspace. It explains strong state responses as the result of a different sensitivity: preoccupation with an existential threat, which produces a willingness to accept operational risks.